2017
DOI: 10.1002/2016gc006793
|View full text |Cite
|
Sign up to set email alerts
|

Development of branching brittle and ductile shear zones: A numerical study

Abstract: Continental collision zones are usually associated with large‐scale strike‐slip shear zones. In most cases, these shear zones are complex and consist of multiple strands, varying in width, length, and total displacement. Here we present 2‐D numerical models to simulate the formation of such shear zones at different depth levels within the crust, under either brittle (frictional/plastic) or ductile conditions. Localization of shear zones is initiated by a material contrast (heterogeneity) of the material parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 130 publications
(185 reference statements)
4
31
0
Order By: Relevance
“…Irregular movement of such blocks can lead to both relative rotation and variation in principal stress directions within blocks, which could explain the difference in preserved shortening direction observed in the low‐strain area II in Figure . Numerical studies have shown that due to the interaction of individual shear zone strands, the principal shortening direction inside the shear zones may rotate and lead to further stress perturbations (Meyer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Irregular movement of such blocks can lead to both relative rotation and variation in principal stress directions within blocks, which could explain the difference in preserved shortening direction observed in the low‐strain area II in Figure . Numerical studies have shown that due to the interaction of individual shear zone strands, the principal shortening direction inside the shear zones may rotate and lead to further stress perturbations (Meyer et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The maximum compressive stress σ 1 is initially oriented at an angle of 45 • to the imposed shear direction, indicated by the light green arrows in Fig. [2] (e.g., Meyer et al, 2017). Values of the reference model parameters (Table 1) are set largely in accordance with Lapusta et al (2000), with differences in the choice of V 0 and the initial mean stress P B .…”
Section: Model Setupmentioning
confidence: 99%
“…In this area diverse fault patterns and fault networks are found. Analog experiments, structural geology and fracture mechanics define a variety of different secondary fault structure types: branching faults, one-sided horsetail splay faults, synthetic and antithetic Riedel faults, splay cracks, wing cracks, and mixed modes (e.g., Cooke, 1997;Hubert-Ferrari et al, 2003;Kim et al, 2004;Mitchell and Faulkner, 2009;Aydin and Berryman, 2010;Perrin et al, 2016b, Fig. 1b, c, d).…”
Section: Introductionmentioning
confidence: 99%
“…Field observations indicate that the damage fan width scales with accumulated fault displacement (Perrin et al, 2016b, a). At a smaller distance from each fault, an inner damage zone of microfractures also develops, whose width does saturate at a few hundred meters for larger displacements (Mitchell and Faulkner, 2009;Savage and Brodsky, 2011;Ampuero and Mao, 2017). During an earthquake, energy is dissipated in the damage zone over large distances from the fault (Cappa et al, 2014;Ampuero and Mao, 2017).…”
Section: Introductionmentioning
confidence: 99%